Modeling of protein complexes in CAPRI Round 37 using template‐based approach combined with model selection. (23rd September 2017) - Dapkūnas, Justas; Olechnovič, Kliment; Venclovas, Česlovas
Abstract: We participated in Round 37 of the Critical Assessment of PRediction of Interactions (CAPRI), held jointly with the 12th edition of the Critical Assessment of protein Structure Prediction (CASP12), having two major objectives. First, we intended to test the utility of our PPI3D web server in finding and selecting templates for comparative modeling of structures of protein complexes. Our second aim was to evaluate the ability of our model accuracy estimation method VoroMQA to score and rank structural models for protein‐protein interactions. Using sequence search in PPI3D and HHpred servers we identified multimeric templates for 7 of 11 CAPRI targets, and models of at least acceptable quality were constructed for 6 of them. The clustering and visual analysis features implemented in the PPI3D software were instrumental in detecting alternative protein‐protein interaction interfaces among the identified templates. When a single binding mode was observed for homologous proteins, the structural modeling of the protein complex was fairly straightforward, whereas choosing the correct interaction template from several alternatives turned out to be a difficult task requiring manual intervention. The combination of full structure and interaction interface VoroMQA scores effectively ranked structural models of protein complexes and selected models of better quality from the CAPRI Scoring sets. The overall results show possible uses of PPI3D and VoroMQA in structural modeling of protein‐protein interactions and suggest ways for further improvements of both methods.